IoT-enhanced music therapy: Utilizing genetic algorithms for personalized violin instruction and mental health adjustment - Wang, Yuan (Alexandria engineering journal, 2025)
Technological developments have recently impacted all sectors, especially education. Different forms of technology can readily be incorporated into the practice, improving the teaching techniques while increasing the learner’s results. This research aims to explore students’ capacity to change their mental health, especially in violin teaching at a professional level. This study proposed on the secret dynamics behind mental health adjustment for violin students, leveraging technological transformation, particularly the Internet of Things (IoT) and genetic algorithms (GA), to transform enjoyment. Music education, which involves learning a musical instrument such as the violin, affects the psychological development of students. The journey of music education is emotional and cognitive development, and stress management opens up the area for productive research about technology and mental issues. Within the paradigm of educational diversity, there is a growing need to investigate many anomalous yet potentially effective fields for addressing students’ improvement. In violin teaching, the immediate acquisition of physiological and emotional reactions drives the implementation of IoT. On the other hand, a genetic algorithm is an intelligent tool that reveals patterns in this information and identifies hidden relationships between instructional variables and the student’s mental health. A holistic approach to applying the ACSI psychological adjustment ability test model is based on a three-level analysis theory of psychological adjustment abilities and positive environmental theory. The comprehensive analysis of 90 categories related to SCL-90 and SRHMS allows for studying the ability to adapt mental status regarding violin teaching among the students.